Skyglow inside your eyes: intraocular scattering and artificial brightness of the night sky - Salvador Bará; Carmen Bao-Varela (International Journal of Sustainable Lighting, 2023)
The visual perception of the natural night sky in many places of the world is strongly disturbed by anthropogenic light. Part of this artificial light is scattered in the atmosphere and propagates towards the observer, adding to the natural brightness and producing a light polluted sky. However, atmospheric scattering is not the only mechanism contributing to increase the visual skyglow. The rich and diverse biological media forming the human eye also scatter light very efficiently and contribute, in some cases to a big extent, to the total sky brightness detected by the retinal photoreceptors. In this paper we quantify this effect and assess its relevance when the eye pupil is illuminated by light sources within the visual field. Our results show that intraocular scattering constitutes a significant part of the perceived sky brightness at short distances from streetlights. These results provide quantitative support to the everyday experience that substantial gains in naked-eye star limiting magnitudes can be achieved by blocking the direct light from the lamps that reaches the eye pupil.